Retreating Glacier and Advancing Forest Over the Past 200 Years in the Central Himalayas. Issue 9 (2nd September 2020) - Sigdel, Shalik Ram; Zhang, Hui; Zhu, Haifeng; Muhammad, Sher; Liang, Eryuan
Abstract: The Himalayan glaciers, as unique reservoirs of freshwater for densely populated Asian countries, have been receiving considerable attention in public and scientific research. However, little is known about their long‐term fluctuations as related to climate variability. Herein, we reconstructed glacier fluctuation events by tree ring‐based moraine dating and repeated photographs. We assessed these fluctuations over the past 200 years in the Gangapurna and Annapurna III glaciers, located in the central Himalayas. We detected five major glacier fluctuation events in the 1790s, 1920s, 1930s, 1960s, and 1970s. A higher rate of glacier recession was observed from the 1980s onward, coinciding with climate warming. As shown by repeated photographs, the retreating rate of the Gangapurna glacier from 1979 to 2016 (up to 24.4 m yr −1 ) is much higher than the Annapurna III glacier (7.54 m yr −1 ) from 1950 to 2016. Their different frontal retreat rates were likely related to microtopography and glacier sizes. Older moraines developed during and after the Little Ice Age (LIA) were already covered by dense forest, presenting the evidence for retreating glaciers and advancing forests in the central Himalayas. Ongoing warming tends to speed up such ecological processes by resetting biophysical environment of the deglaciated forefields. In general, glaciers have shown retreating trends over the last 200 years, presenting a risk for preserving water resources in the Himalayas and nearby regions. Alternatively, advancing forest tends to amplify warming rate by reducing albedo, which is a new issue for investigating ecohydrological feedbacks between mountain forests, climate, and water resources. Plain Language Summary: The Himalayan glaciers, as unique reservoirs of freshwater, have been receiving considerable attention in public and scientific research. However, there is a huge knowledge gap on long‐term glacier fluctuations. For example, Intergovernmental Panel on Climate Change (IPCC) in its Fourth Assessment Report asserted that glaciers in the Himalayas will likely disappear by the year 2035 under the present rate of glacier recession. This statement raised scientific criticisms and presented the necessity to have a better understanding on past glacier fluctuations. However, little is known about long‐term glacier fluctuations and ecological processes on the deglaciated forefields. Herein, we reconstructed glacier fluctuation events by tree ring‐based moraine dating and repeated photographs for the Gangapurna and Annapurna III glaciers over the past 200 years in the central Himalayas. This study presents the first detailed evidence for the fluctuation history of Himalayan glaciers over the past 200 years. According to the minimum age of the moraines, the glacier retreat occurred during the 1790s with successive recessions during the 1920s, 1930s, 1960s, and 1980s. The central Himalayas are characterized by retreating glaciers and advancing forest during the past 200 years, presenting a challenge for ecological assessment and resource management. Key Points: History of Himalayan glacier fluctuations over the past 200 years were evidenced by tree ring Five major glacier fluctuation events were dated in the 1790s, 1920s, 1930s, 1960s, and 1970s and a higher rate of recession was observed during the recent decades The central Himalayas is characterized by retreating glaciers and advancing forests over the past 200 years